Kelimpahan Populasi Hama Kutu Putih Phenacoccus manihoti Matile-Ferrero, Paracoccus marginatus Williams dan Granara De Willink (Hemiptera: Pseudococcidae) serta Kumbang Predator Scymnus Sp. (Mulsant) (Coleoptera: Coccinellidae) pada Ubi Kayu di Kabupaten - Simare-Mare, Rut Megawati; Widaningsih, Dwi; Sunari, A. A. Ayu Agung Sri (Agrotrop : Journal on Agriculture Science, 2023)
Population of Mealybugs Phenacoccus manihoti Matile-Ferrero , Paracoccus marginatus Williams and Granara De Willink (Hemiptera: Pseudococcidae) and Predatory Beetle Scymnus sp. (Mulsant) (Coleoptera: Coccinellidae) on Cassava in Badung Regency. Cassava ( Manihot esculenta Crantz) is a food crop commodity as an important carbohydrate source in Indonesia. This study aims to determine the population of mealybugs P. manihoti and P. marginatus and the population of predatory beetles as natural enemies of plants. cassava in Bali. The research was carried out from December 2021 to February 2022 in Badung Regency, Kuwum village, Mengwi sub-district, Bali Province. The method used in the sample is a purposive sampling with method diagonally. The results showed that the abundance of mealybugs P. marginatus and P. manihoti was quite high with a population abundance of 949.4 and 466.6. The abundance of predatory populations of scymnus sp. classified as low where 3 predators were found in the Adira 1 variety and 2.4 predators were found in the Malang variety 6. The functional relationship between the mealybug population P. marginatus , P. manihoti and the predator Scymnus sp. had a positive relationship and strong with a coefficient correlation interval was 0.9219 for P. marginatus and 0.995 for P. manihoti .